2016
DOI: 10.1177/1947603516665442
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-up of Knee Joint Distraction: Clinical Benefit and Cartilaginous Tissue Repair in an Open Uncontrolled Prospective Study

Abstract: Objective In end-stage knee osteoarthritis, total knee arthroplasty (TKA) may finally become inevitable. At a relatively young age, this comes with the risk of future revision surgery. Therefore, in these cases, joint preserving surgery such as knee joint distraction (KJD) is preferred. Here we present 5-year follow-up data of KJD. Design Patients ( n = 20; age <60 years) with conservative therapy resistant tibiofemoral osteoarthritis considered for TKA were treated. Clinical evaluation was performed by questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 27 publications
2
83
0
1
Order By: Relevance
“…Three studies consisting of one cohort study and two randomized controlled trials were identified as meeting inclusion criteria [11][12][13] (►Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies consisting of one cohort study and two randomized controlled trials were identified as meeting inclusion criteria [11][12][13] (►Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…10 It is reported that this temporary mechanical unloading allows natural intrinsic repair processes to regenerate cartilaginous tissue evidenced by a sustained clinical benefit and increase in joint width space. 11 With KJD being a joint sparing procedure aimed at postponing a first prosthesis, successful clinical adoption could significantly improve patients' quality of life and thus reduce the long-term health care costs associated with knee OA.…”
mentioning
confidence: 99%
“…Despite the smaller initial JSW increase in patients who underwent TKA after KJD, their JSW was on average not decreased compared to baseline at the last measurement before TKA. This should be considered in the context of a general decrease in JSW over time as natural course of joint degeneration in case the disease remains untreated 7 .…”
Section: Discussionmentioning
confidence: 99%
“…MRI scans were performed with the Eckstein protocol 6,12 . The mean cartilage thickness over the subchondral bone area and the percentage of denuded subchondral bone area were calculated for the MAC 7 .…”
Section: Radiographic and Quantitative Mri Analysismentioning
confidence: 99%
“…The long-term effects may be greater; for example, the reduction in joint contact forces via weight loss, wedged insoles, unicompartment offloader braces, or high tibial osteotomy has been shown to reduce structural damage and improve tissue remodeling, increasing the potential of the joint to restore normal function [15]. A brace that is capable of unloading the knee joint may allow for improved soft-tissue repair [56], or be used as a rehabilitation tool to help improve strength and range of motion while weight-bearing. Rehabilitation protocols highlight the need for progressive weight bearing, passive extension, quadriceps control and neuromuscular training following knee procedures including meniscal repair [57], anterior cruciate ligament reconstruction [58], and articular cartilage repair [59][60][61][62][63][64], all of which may be aided by the TCU's powerful and adjustable knee extension assist mechanism.…”
Section: Unloading Provided By the Tricompartment Unloadermentioning
confidence: 99%